Immunization Strategies against Piscirickettsia salmonis Infections: Review of Vaccination Approaches and Modalities and Their Associated Immune Response Profiles - Evensen, Øystein (Frontiers in Immunology, 2016)
Salmonid rickettsial septicemia (SRS) is a serious, infectious disease in Chilean salmon farming caused by Piscirickettsia salmonis, causing heavy losses to the salmonid industry. P. salmonis belongs to the Gammaproteobacteria, order Thiotrichales. SRS was first described in Chile in 1989, and infection with P. salmonis has since been described from a high number of fish species and in several geographic regions globally. P. salmonis infection of salmonids causes multifocal, necrotic areas of internal organs such as liver, kidney, and spleen. Histologically and immunologically, the tissue response is the formation of granulomas, often with central suppuration. The exact sequence of infection is not known, but bacteria likely gain access to internal organs through mucosal surfaces and when infected, fish carry bacteria in macrophages. It has not been fully determined if the bacterium resides in the cytosol or “hide” within vesicular structures intracellularly, although there are indications that in vitro infection results in actin reorganization and formation of actin-coated vesicle within which the bacterium resides. Protection against lethal challenge is well documented in lab scale experiments, but protection from vaccination has proven more difficult to attain long term under field conditions. Current vaccination protocols include whole cell, inactivated and adjuvanted vaccines for injection for primary immunization followed by oral boost where timing of boost delivery is followed by measuring circulating antibody levels against the pathogen. Documentation also exist that there is correlation between antibody titers and protection against mortality. Future vaccination regimes will likely also include live-attenuated vaccines or other technologies such as DNA vaccination. So far, there is no documentation available for live vaccines and, for DNA vaccines, studies have been unsuccessful under laboratory conditions.